An Empirical Study on Selecting Partially Equivalent (PE) Benchmarks for Mutual Funds Categories in Pakistan: ANOVA Approach - Ahmed, W. S.; Paracha, A. T.; Sheikh, J.; Azeam, M. F.; Saboor, M. J. (The Nucleus, 2017)
In this study, we propose a new concept of partially equivalent (PE) benchmarks for evaluation different mutual funds categories in Pakistan. We constructed separate benchmarks for all major categories of funds after carefully considering the asset composites of classes. For the validity of proposed benchmarks, we conducted unit root test, kernel density distribution and ANOVA analysis. Our results prove that money market and aggressive income non-sharia benchmarks and most of Sharia benchmarks indices have shown indifference of distribution against the conventional benchmark i.e. KSE 100 and KMI 30. This encourage the fund managers and scholars alike to use the proposed benchmark indices against the conventional ones to analyze the management style, market variations, market timing and behavioral aspects with some precision and accuracy.